Development of Scientific Process Skill Assessment Instrument on Stoichiometry Using Rasch Model in the Merdeka Curriculum - Pertiwi, Nadia; Aini, Faizah Qurrata (Journal of Educational Sciences, 2025)
The achievement of learning outcomes in the Merdeka Curriculum with respect to the assessment of scientific process skills remains unobservable. Teachers frequently conduct assessments that focus primarily on students' knowledge, while assessments targeting scientific process skills are rarely implemented. This is concerning because scientific process skills is part of the learning outcomes expected in the Merdeka Curriculum. Furthermore, there is a lack of assessment instruments in the form of tests that could assist teachers in measuring students' scientific process skills. This study used a research and development method using the Rasch model. The assessment instrument consisted of 24 multiple choice questions. The study involved three chemistry lecturers from the FMIPA at Universitas Negeri Padang, two chemistry teachers, and students from SMA Negeri 5 Padang as research subjects. Field test results were analyzed using Ministep software, which demonstrated that all items met the criteria for validity (based on outfit MNSQ, ZSTD, and Pt Mean Corr), reliability, varied difficulty levels (ranging from very difficult to very easy), and good item discrimination indices.